A Note on the Effects of the Income Stabilisation Tool on Income Inequality in Agriculture. (6th April 2014) - Finger, Robert; El Benni, Nadja
Abstract Increasing concerns with income risks in agriculture have led to discussions on the introduction of an Income Stabilisation Tool (IST) in Europe. In this note, we extend existing evaluations of the IST by investigating the potential effect of the IST on inequality in farm incomes using Swiss agriculture as a case study. We find that the IST will significantly reduce income inequality, in particular by increasing lower quantiles of the income distribution. This property constitutes a value‐added of the IST that is not yet considered in the current policy debate.